Sistem Terpadu Web Dan Android Sebagai Inovasi Pemasaran Produk Umkm Dan Profil Bisnis Unggulan Kabupaten Sigi : Integrated Web and Android System as Product Marketing Innovation MSMEs and Leading Business Profiles of Sigi Regency - Kade Dwi Arsana, I Gusti Ngurah Agung; Wirdayanti; Syahrullah; Ngemba, Hajra Rasmita; Hendra, Syaiful (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
The digital transformation era has fueled enthusiasm for digital living among Indonesian society, driven by the surging use of internet and smartphones. The digital economy has unlocked new opportunities for businesses and entrepreneurship, significantly boosting national economic growth. In this context, MSMEs (Micro, Small, and Medium Enterprises) play a pivotal role as the backbone of Indonesia's economy, holding immense potential to drive national progress. The year 2024 has been designated as the year of digital transformation for MSMEs, with a target of integrating 30 million MSMEs into the digital ecosystem. Sigi Regency, with its 30,554 MSMEs spanning diverse business sectors, is a key focus for the local government's efforts to digitize the MSME sector, aiming to enhance product quality, services, and global competitiveness. To achieve this goal, an integrated web and Android system is proposed, empowering MSMEs to independently manage product data and business profiles, creating a digital gallery to showcase the Sigi MSME catalog.